Corporate Governance and Responsible Bankers: Lesson Learned from Lehman Brothers' Minibonds Saga - Ho, Angel / W.Y. (2009)
The focus of this research is the case of Lehman Brothers’ Minibonds Saga in Hong Kong which directly followed the current economic crisis. Such a study is important to identify the problems faced by Hong Kong since the collapse of Lehman Brothers in US and to reflect on the lessons learned from the case. The research then seeks to identify the enablers in respect of responsibilities from economic, legal, ethical, social and management/administration perspectives contributed to the Minibonds case, by which explore the important role corporate social responsibility plays in the financial market. The research approach adopted in this dissertation includes empirical interviews and secondary data analysis. The findings from this research provide evidence that there is inherent market inefficiency in the banking sector. The main conclusions drawn from this study suggest the important role corporate social responsibility plays in the financial market in Hong Kong and highlight that effective corporate governance system should be embedded with corporate social responsibilities so as to bridge the existing information gap and restore the current trust crisis achieve market efficiency within the banking sector of Hong Kong. This dissertation recommends that ethical and responsible behavior in management practices is essential to restore trust and achieve market efficiency in the financial market.